2020
DOI: 10.1039/c9fo02924a
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity effects of red seaweed, Plocamium telfairiae, in C57BL/6 mice fed a high-fat diet

Abstract: This study aimed to demonstrate the anti-obesity effect of Plocamium telfairiae (PT), a red seaweed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…We demonstrated the potential of (−)-loliolide to reduce expression of lipogenic protein SREBP-1 and adipogenic proteins PPAR-γ, C/EBP-α, and FABP4. These results are consistent with previous publications reporting hypolipidemic and anti-obesity activity of (−)-loliolide [58]. Furthermore, we found that the lipolytic p-HSL and thermogenic PGC-1α protein expressions were higher in 3T3-L1 cells treated with a low concentration of (−)-loliolide suggesting that the range of 0.125 to 0.25 µg/mL is a critical concentration.…”
Section: Discussionsupporting
confidence: 93%
“…We demonstrated the potential of (−)-loliolide to reduce expression of lipogenic protein SREBP-1 and adipogenic proteins PPAR-γ, C/EBP-α, and FABP4. These results are consistent with previous publications reporting hypolipidemic and anti-obesity activity of (−)-loliolide [58]. Furthermore, we found that the lipolytic p-HSL and thermogenic PGC-1α protein expressions were higher in 3T3-L1 cells treated with a low concentration of (−)-loliolide suggesting that the range of 0.125 to 0.25 µg/mL is a critical concentration.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to a significant decreasing in body weight of C57 BL/6J male mice, as well as reducing white adipose tissue (WAT) weight, e.g., fatty liver, leptin, total cholesterol, and serum triglycerides contents in vivo without cytotoxic effect [ 79 ]. Forty % of Plocamium telfairiae ethanolic extract showed anti-obesity ability via reducing the fat accumulation and suppressed the expression of major adipogenesis factors, like peroxisome proliferator-activated receptor-γ (PPAR-γ),CCAAT/enhancer-binding protein (C/EBP)-α, sterol regulatory element-binding protein 1 (SREBP-1), and phosphorylated ACC (pACC) in 3T3-L1 cells [ 80 ]. Seo et al [ 81 ] demonstrated the antidiabetic activity of extract from Gelidium amansii via reduction the accumulation of lipid in 3T3-L1 adipocyte cell line.…”
Section: Anti-obesity Activitymentioning
confidence: 99%
“…Our findings suggest that ST treatment may effectively reduce the risk of type 2 diabetes by controlling blood glucose levels in HFD-induced obese mice. Moreover, excessive fat accumulation is a marker of obesity, which can increase fatty liver and the size of white adipocytes [33,34]. Our results show that oral administration of ST in HFD-induced obese mice improved fatty liver and decreased fat accumulation.…”
Section: Discussionmentioning
confidence: 58%